2021
DOI: 10.2478/sjph-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Persons with intellectual disability: Sexual behaviour, knowledge and assertiveness

Abstract: Background Persons with ID most often have incomplete, contradictory and imprecise knowledge of sexuality and sexual intercourse itself. They are not provided with sufficient information on their own body and sexuality, and are often discouraged from and sanctioned for trying to sexually express themselves. Sexual abuse due to low sexual assertiveness is also common. Aim The principal aim of this study was to establish the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
1
12
1
Order By: Relevance
“…Some of the participants re ected on their di culties nding someone to have a romantic relationship with, and the risks they exposed themselves to in this search. These results may explain why so many people with intellectual disabilities have sex they do not want to have (19). This study reveals that the participants lacked essential knowledge related to consent, which we suggest is crucial in decreasing the risk of sexual abuse.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Some of the participants re ected on their di culties nding someone to have a romantic relationship with, and the risks they exposed themselves to in this search. These results may explain why so many people with intellectual disabilities have sex they do not want to have (19). This study reveals that the participants lacked essential knowledge related to consent, which we suggest is crucial in decreasing the risk of sexual abuse.…”
Section: Discussionmentioning
confidence: 77%
“…It has been found that one in three adults with intellectual disabilities has experienced sexual abuse, and that their abusers were often people with intellectual disabilities as well (18). In a study of 100 participants with intellectual disabilities, Brkić-Jovanović, Runjo (19) found that 82 % were sexually active, and that most of them had had sex they did not want to. In instances of sexual abuse, it is crucial that the police are aware of any intellectual disabilities in the early stages of a criminal case because this can affect the verdict (20).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the participants reflected on their difficulties finding someone to have a romantic relationship with, and the risks they exposed themselves to in their search. This results may explain why so many people with intellectual disabilities have sex they do not want to have [ 25 ]. This study reveals that the participants lacked essential knowledge related to sexual consent, which we suggest is crucial in decreasing the risk of sexual abuse.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that one in three adults with intellectual disabilities has experienced sexual abuse, and that their abusers were often people with intellectual disabilities as well [ 24 ]. In a study of 100 participants with intellectual disabilities, Brkić-Jovanović, Runjo [ 25 ] found that 82% were sexually active and that most of them had had sex they did not want to due to reduced assertiveness skills. In instances of sexual abuse, it is crucial that the police are aware of any intellectual disabilities in the early stages of a criminal case because this can affect the verdict [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, PIFD who have had a partner have had the opportunity to experience, more or less, healthy relationships, what it feels like to be loved, and improvement in their communication skills. They have practiced respect and assertiveness, as they may have had to respond to requests for unwanted sexual practices and may even have been treated inappropriately by tolerating unhealthy and unacceptable dynamics (Brkić-Jovanović et al, 2021;Rushbrooke et al, 2014). People who participate in affective-sexual education programs while in a relationship have the opportunity to practice many of the skills and attitudes that are taught in the course.…”
Section: Introductionmentioning
confidence: 99%